Comparative Review on Structure, Properties, Fabrication Techniques, and Relevance of Polymer Nanocomposites Reinforced with Carbon Nanotube and Graphite Fillers. (22nd January 2016) - Naz, Asima; Kausar, Ayesha; Siddiq, Muhammad; Choudhary, Muhammad Aziz
ABSTRACT: Owing to their remarkable electrical, mechanical, thermal, catalytic, and optical properties as well as their unique structure, carbon nanotubes and graphite have been exploited to produce high performance and multifunctional composites. The resultant composites are differentiated on the basis of their properties to meet various applications. In the framework of this review article, we have mainly focused on the preparation, structure, and properties of two families of composite materials with an emphasis on the differences between them. Moreover, the current challenges, future prospectives, and applications of carbon nanotubes- and graphite-based materials in sensors and in photovoltaic and energy storage devices (Li-ion battery) have been discussed. GRAPHICAL ABSTRACT: